Comparison of creatine kinase elevation caused by Janus kinase inhibitors and interleukin-6 inhibitors in patients with rheumatoid arthritis: A propensity score-matched study - Masahiro Tada; Tadashi Okano; Kenji Mamaoto; Yutaro Yamada; Kazuki Orita; Koji Mandai; Shohei Anno; Takahiro Iida; Kentaro Inui; Tatsuya Koike (Archives of Rheumatology, 2024)
Objectives: This study aimed to examine whether creatine kinase (CK) elevation occurs with interleukin (IL)-6 inhibitors, as in Janus kinase (JAK) inhibitors, which are reported to increase CK levels in rheumatoid arthritis. Patients and methods: A multicenter database of JAK inhibitor and IL-6 inhibitor treatment was retrospectively searched between January 2016 to December 2022; 142 cases (117 females, 25 males, mean age: 63.8±13.0 years; range, 20 to 85 years), with 71 cases in each group, were extracted by propensity score matching using age, sex, body mass index, and CK at 0 weeks. The outlier rate was compared. Patients’ background characteristics related to elevated CK levels at 24 weeks were investigated by univariate and multivariate analyses. Results: Creatine kinase levels at 4 and 12 weeks were significantly higher with JAK inhibitors than with IL-6 inhibitors (four weeks, 72 vs. 87.5 IU/mL, p=0.016; 12 weeks, 71 vs. 95.5 IU/mL, p=0.028). The outlier rate (Grade 1) with JAK inhibitors increased significantly over time (0 weeks, 4.2%; four weeks, 18.1%; 12 weeks, 21.7%; 24 weeks, 18.3%; p=0.015), whereas that with IL-6 inhibitors increased slightly (0 weeks, 5.6%; four weeks, 9.2%; 12 weeks, 8.6%; 24 weeks, 8.5%; p=0.745), with a significant difference between the groups (p=0.035). No patients discontinued treatment due to myalgia or renal dysfunction. The factors significantly positively related to elevated CK levels at 24 weeks were male sex and creatinine. Those significantly negatively related were Steinbrocker stage and class, modified health assessment questionnaire scores, estimated glomerular filtration rate, and glucocorticoid dose. Conclusion: Mild CK elevations with JAK inhibitors are not a particular clinical problem. CK elevation might be specific to JAK inhibitors.